Decision Support Systems to Determine Electronic Sales Products using The TOPSIS Method - Pangaribuan, Andi Pranata; Rita Hamdani (Login : Jurnal Teknologi Komputer, 2023)
Products are everything that is traded. One of the tradable products is electronic products. One of the shops that sells electronic products in Medan is the Asia Electric Shop. The Asia Electric shop which sells electronic goods such as lamps, electrical appliances, furniture and so on. In fulfilling product stock in the store, order products that match the product category to be sold directly to the factory. This will cause a large stock of products in the warehouse. So that the Asian Electric Shop Owner has not been able to determine the exact electronics sales product. The owner must determine the right product sales and suitable for sale in the market, because the sale of products is part of company management and is also a very important factor that will directly affect the smooth running or confidence of the store in being successful. Therefore we need a "decision support system in determining electronic sales products using the Topsis method. So the author is the author of Decision Support Systems to Determine Seller Products using the Topsis method. The program used is Visual Basic 2010 and uses Microsoft SQL Server 2008 as its database. With this system, it is hoped that the Asia Electric Shop can easily determine the sales product.